Effects of Different LVEF Assessed by Echocardiography and CMR on the Diagnosis and Therapeutic Decisions of Cardiovascular Diseases - Zhao, Lei; Lu, Aijia; Tian, Jie; Huang, Jie; Ma, Xiaohai (Frontiers in Physiology, 2020)
Aims: The impact of different left ventricular ejection fraction (LVEF) assessed by echocardiography (EC) and cardiac magnetic resonance (CMR) on clinical diagnosis and management that could be critical in clinical practice remains unclear. This study investigated this impact for patients who underwent both exams in a real-world clinical practice. Methods: 500 patients who underwent CMR and two-dimensional EC were retrospectively included in present study. EC-measured LVEF and CMR-measured LVEF were compared. A 50% cut-off of LVEF was chosen to assess the effect of the difference between these two modalities on disease diagnosis, and a 35% cut-off was chosen for disease management, respectively. For those patients who received device therapy or coronary artery bypass grafting (CABG), the study compared the LVEF between EC and CMR with the current guideline for therapy recommendation. Results: EC-LVEF and CMR-LVEF were positively correlated, but EC-LVEF was significantly larger than CMR-LVEF (P<0.001). Three patient groups were examined: (I) CMR-LVEF≥50%, (II) 35%<CMR-LVEF<50%, and (III) CMR-LVEF≤35%. Overall, 139 of 500 patients showed inconsistent measures. There were more inconsistent measures between the two modalities in group III than group I (41.6% for group III vs. 4.1% for group I). In patients who received device therapy or CABG, 97.6% of the CMR-measured LVEF were consistent with the guideline, but only 61.0% consistent EC-measured LVEF. Conclusions: For patients with lower LVEF and planning to receive device therapy or cardiac surgery, it should be cautious to applying the recommended cut-off values to CMR-measured LVEF because its inconsistency with EC-measured LVEF.